Academic Senate Minutes 2003-09-18 - Academic Senate:::::::::
Report from the Chair. Agenda amended and approved. Minutes of 4/24; 5/8; 5/22; 9/4 approved. Report from President, Provost, Associate Students, Chair-Elect and Statewide Senator. Christine Renaudin approved for three year term as Academic Council on International Programs Representative for SSU. Resolution Opposing Prop 54 first reading waived, motion passed. From S&F: By-laws change to SSP rep for APC approved. Constitutional Amendment: Lecturer Eligibility for Voting and Service tabled.